Exit, Voice, and Loyalty in the Indo-Pacific: Shaping Future Regional Policies - Delviolin, Ellie Ophelia; Tangka, George Morris William (Global South Review, 2024)
This study investigates public behavior in Indo-Pacific countries, employing the Exit, Voice, and Loyalty framework. In an era marked by globalization and interconnectedness, citizen choices and actions in the Indo-Pacific region are increasingly influenced by global trends and international relations. Trust in government plays a pivotal role, affected by public scrutiny in an interconnected world and impacting trust levels. Life satisfaction, a reflection of individual well-being, mirrors government performance and is a critical factor. Quantitative analysis, including multinomial logistic regression, using data from the Asian Barometer Survey 2008 unveils noteworthy results. Lower trust in government reduced life satisfaction, and negative government assessments drive exit behavior, with a 15% increase in the likelihood of citizens choosing to exit when trust is low. Conversely, higher life satisfaction and positive government assessments increase the probability of loyalty behavior by 20%, while voice behavior likelihood decreases by 10%. These findings provide valuable insights into public behavior in the Indo-Pacific, emphasizing the roles of trust, life satisfaction, and government performance, supported by numerical evidence. These insights hold significance in the Indo-Pacific's ever-evolving global landscape, serving as a foundation for policymaking and decision-making. Policymakers and researchers can use this knowledge to enhance governance, promote societal well-being, and deepen citizen-government connections in the dynamic Indo-Pacific region.Keywords: Indo-Pacific; Exit Voice and Loyalty Framework; life satisfaction; government performance; trust